DEPICTING PATRIARCHY : THE STRUGGLES AND RESISTANCE OF WOMEN IN ARUNDHATI ROY’S “THE GOD OF SMALL THINGS” - Choudhury, Ashraful Alam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The novelists depicted a verypathetic picture particularly with reference to the women who lived surrounding us. They painted a gloomy and shadowy world for women. Women were portrayed as if they were devoid of artistic creation. They were only considered as the object of sex. This predicament of women in the 1970s compels the Indian women writers to pen down their voice against the male dominated patriarchal society. Women writers have succeeded in great extent in changing the attentions of the readers to the evil practice of patriarchy by describing the life of Indian women. My paper is a humble attempt to show how female protagonists Rahel in Arundhati Roy's 'The God of Small Things' struggle for their existence in the society in various roles against the male dominated patriarchal society.